2013
DOI: 10.1089/jamp.2011.0942
|View full text |Cite
|
Sign up to set email alerts
|

Sputum Tobramycin Concentrations in Cystic Fibrosis Patients with Repeated Administration of Inhaled Tobramycin

Abstract: Background: Dosing of tobramycin solution for inhalation (TSI) in cystic fibrosis (CF) patients was based on single-dose pharmacokinetic studies. This investigation was prompted by evidence of possible antibiotic accumulation in respiratory secretions with repeated dosing. The objectives were to evaluate whether tobramycin accumulates in respiratory secretions with repeated inhalation, compare total and biologically active tobramycin concentrations in CF sputum, and evaluate sputum induction for obtaining secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…In particular, mannitol (Barraud et al, 2013) and arginine (Lebeaux et al, 2014) have been shown to resensitize P. aeruginosa biofilms to aminoglycosides; however, in the case of mannitol, most of the effect seemed to be due to osmotic effects, and arginine required very high aminoglycoside concentrations. In contrast, fumarate appears to potentiate tobramycin in the physiologically relevant concentration ranges achievable by intravenous (Vandenbussche and Homnick, 2012) or inhaled administration (Ruddy et al, 2013). Finally, although the present work primarily focuses on fumarate, we anticipate that other lower TCA cycle and lower glycolysis carbon sources could also have therapeutic value as potential adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, mannitol (Barraud et al, 2013) and arginine (Lebeaux et al, 2014) have been shown to resensitize P. aeruginosa biofilms to aminoglycosides; however, in the case of mannitol, most of the effect seemed to be due to osmotic effects, and arginine required very high aminoglycoside concentrations. In contrast, fumarate appears to potentiate tobramycin in the physiologically relevant concentration ranges achievable by intravenous (Vandenbussche and Homnick, 2012) or inhaled administration (Ruddy et al, 2013). Finally, although the present work primarily focuses on fumarate, we anticipate that other lower TCA cycle and lower glycolysis carbon sources could also have therapeutic value as potential adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, these agents were the same pharmaceuticals used in the clinical care of CF patients. Antibiotic concentrations tested in the biofilm and planktonic samples were 100 g/ml tobramycin (TOBI; Novartis) and 20 g/ml azithromycin (APP Pharmaceuticals), which are concentration ranges observed in CF sputum (29,30). DNase concentration tested was 30 g/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Future direction towards an efficient aerosol antibiotic treatment comes from a group of patients in need of daily treatment. Studies in children and young adults with cystic fibrosis indicate that the next generation of aerosol antibiotic treatments should be delivered in less time and less dose frequency during the day 144. Moreover, a patient-friendly device that increases adherence and possibly enables monitoring of treatment should be investigated further 118.…”
Section: Resultsmentioning
confidence: 99%